Alternative notions of sexuality and personhood: the case of Bal Gandharva. Issue 3 (3rd July 2018) - Devare, Aparna
ABSTRACT: This article examines the meteoric rise and enormous popularity of a Marathi stage actor and singer, Bal Gandharva, in early twentieth-century western India. Gandharva was distinctive because he was a male artist who dressed and acted as a woman on stage and was adulated by both women and men for his powerful female roles. The article argues that Gandharva embodied 'fuzzy' boundaries between man and woman, drawing from indigenous traditions of gender fluidity. While maintaining strict boundaries between being a man in his personal life and a woman on stage, Gandharva tapped into alternative notions of masculinity. I argue that the adulation he experienced for his acting and singing as a woman points to transgressive possibilities in the otherwise conservative middle-class imagination and challenges what are colonial constructions of hyper-masculinity.